2008
DOI: 10.1111/j.1365-4632.2008.03675.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the radiometric BACTEC 460 TB culture system and Löwenstein–Jensen medium for the isolation of mycobacteria in cutaneous tuberculosis and their drug susceptibility pattern

Abstract: Radiometric liquid culture medium together with conventional L-J medium may be recommended in practice to enable the institution of appropriate antituberculous therapy modifications in drug-resistant cases of cutaneous tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 27 publications
1
31
2
5
Order By: Relevance
“…Mycobacterium tuberculosis akan tumbuh dalam 3-4 minggu dengan media tersebut. Sebuah penelitian prospektif yang dilakukan oleh Aggarwal P dkk, 16 26 mycobacterium berhasil diisolasi dari 35 pasien. Hanya 25,7% hasil biakan positif pada media LowensteinJensen dengan rata-rata periode pertumbuhan 31,5 hari.…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Mycobacterium tuberculosis akan tumbuh dalam 3-4 minggu dengan media tersebut. Sebuah penelitian prospektif yang dilakukan oleh Aggarwal P dkk, 16 26 mycobacterium berhasil diisolasi dari 35 pasien. Hanya 25,7% hasil biakan positif pada media LowensteinJensen dengan rata-rata periode pertumbuhan 31,5 hari.…”
Section: Pembahasanunclassified
“…Kombinasi antara obat antituberkulosis seperti isoniazid dengan dihidrostreptomisin atau klaritromisin dapat digunakan. 7,9,11,14,16 Terapi selain dengan medikamentosa, obat topikal atau dengan pembedahan juga pernah dilaporkan. Terapi topikal dapat dilakukan dengan kompres air NaCl 0.9% serta perbaikan higiene.…”
Section: Tuberculosisunclassified
“…BACTEC 460TB, BACTEC 960 MGIT sistemleri gibi sıvı kültür sistemlerini LJ besiyeri ile karşılaştıran birçok çalışmada benzer şekilde sıvı besiyerlerinde mikobakteri izolasyon oranı daha yüksek bulunmuştur. 12,[17][18][19] Rodrigues ve ark.nın yaptığı bir araştırmada herhangi bir kültür sisteminde üreme olan 5162 örneğin %97'si BACTEC 460TB sisteminde, %72'si ise LJ besiyerinde üre-miştir. 20 Tek başına BACTEC sisteminde kültür pozitifliği %28 iken, tek başına LJ besiyerinde kültür pozitifliği %3 olarak bildirilmiştir.…”
Section: Bulgularunclassified
“…Birçok araştırmada benzer şekilde LJ besiyerinde kontaminasyon oranı, sıvı kültür sistemlerine oranla daha yüksek bulunmuştur. 12,17,18,23,24 Ancak örnek-lerin çeşitliliğine ve kullanılan dekontaminasyon yöntemine bağlı olarak besiyerlerindeki kontaminasyon oranları da farklılık gösterebilir.…”
Section: Bulgularunclassified
“…[2][3][4] Culture of the organism from lesion of cutaneous tuberculosis is again highly specific but is usually tedious and unrewarding [3,[5][6] though some studies have demonstrated substantially better results. [7][8][9][10][11] A therapeutic trial of antitubercular drugs is frequently used to confirm the diagnosis in difficult cases. [12,13] In cutaneous tuberculosis, the sensitivity of DNA PCR technique has varied from 54% to 100%, and specificity from 80% to 100%.…”
Section: Introduction Introductionmentioning
confidence: 99%